EXPLORING SUSTAINABLE FINANCIAL PRACTICES: A STUDY ON GREEN FINANCE INITIATIVES IN SHANGHAI - Clark, Jonathan; Martin , Alice (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The release of the "Implementation Opinions on Accelerating Shanghai to Build an International Green Finance Hub to Serve the Goal of Carbon Peak and Carbon Neutrality" in October 2021 marked a pivotal moment in Shanghai's green finance trajectory. With ambitious targets set for 2025, Shanghai aims to become a global leader in green financial development by fostering an environment that supports green financing exceeding 1.5 trillion CNY and green insurance guarantees exceeding 1.5 trillion CNY. This will position Shanghai to play a prominent role in both national and global green financial cooperation, establishing itself as a hub for carbon trading, pricing, and innovation. While Shanghai has made significant strides in green finance, this paper identifies lingering challenges and offers strategic recommendations based on the current state of green finance development in the city. By addressing these issues, Shanghai can solidify its status as an international green finance hub and contribute substantially to nationwide green and low-carbon initiatives. This paper offers critical insights to guide Shanghai's journey towards a sustainable financial future.